AN INVESTIGATION INTO THE LANGUAGE LIFE OF OVERSEAS CHINESE IN NORTHERN THAILAND - Juanjuan, Liu; Duangmanee, Katematu (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: To reveal the current situation and underlying causes of language practices among overseas Chinese communities in northern Thailand and to enhance their cultural identification with the Chinese nation, this study focuses on Chinese residents in the region. Method: Employing a mixed-methods approach that integrates fieldwork, questionnaires, and interviews, the study conducts both quantitative and qualitative analyses to examine their linguistic behaviors and identity perceptions. Results: The findings indicate that under the influence of ecological and demographic factors, the originally monolingual system centered on Chinese characters has evolved into a hybrid linguistic environment featuring Thai, local minority languages, English, and Burmese. Nevertheless, due to their relatively recent migration history and geographic isolation in mountainous areas, these communities maintain a stronger foundation in Chinese language and cultural inheritance compared to their counterparts in other parts of Thailand. Novelty: Based on these linguistic characteristics, the study proposes the development of a multi-level, multi-domain, and multi-channel dissemination system for Chinese language and culture, aiming to strengthen ethnic and cultural identity. This research is expected to provide valuable insights and references for future studies on language identity and cultural transmission among overseas Chinese communities.